Design and experiments of 4CJ-1200 self-propelled tea plucking machine - Han, Yu; Xiao, Hongru; Song, Zhiyu; Chen, Qiaomin; Ding, Wenqin; Mei, Song (International Journal of Agricultural and Biological Engineering, 2021)
As agricultural labor is decreasing, famous tea production is nearly hard to sustain and is getting more and more expensive in China. To improve the mechanization of tea plucking, this paper designs a self-propelled track-type tea plucking machine that integrates mechanic, hydraulic and electronics. The main parameters of chassis were optimized based on conditions of tea garden. And, three different kinds of cutter blades were designed and analyzed about vibration performance with finite element software. Also, a rigid-flex mixed motion model was established. Based on the model and plots, it is explicit that: 1) the blades move in a sine law; 2) the blades take a symmetrical deform from middle to end while moving; 3) the deformation increases along the blade from the center to sides. The single factor experiment revealed that both travel speed and speed ratio of cutting and travelling had a significant effect on quality indexes (integrity rate, unpicking rate, stubble unevenness) of plucked tea leaf. By universal rotary combination experiment of quadratic regression, the regression equations of three indexes about two experimental factors were established. And, the comprehensive optimization of three indexes was conducted with software Design expert. The optimal operating parameters of machine are as follow: travel speed is 0.41 m/s, speed ratio of cutting and travelling is 1.06; prediction of three indexes are that integrity rate could be reach to 78.26%, unpicking rate reduced to 0.82%, stubble unevenness reduced to 1.30 mm. The results of verification experiment are that: integrity rate could be reach to 77.41%, unpicking rate reduced to 0.87%, stubble unevenness reduced to 1.23 mm. These test indexes that are very close to the predicted values, all surpass the requests specified in the standard of tea plucking with machine. In all, the optimized parameter set is indeed synthetically optimal one that enables the wide use of this tea plucking machine, which can be used in the tea garden that has a lengthways slope less than 18°, a crosswise slope less than 20°, and a height of tea trees between 50-120 cm. From above, the tea plucking machine investigated in this paper provides an effective solution to present tea picking problem that is the bottleneck of tea industry. Further studies need to do for making this machine more automated and intelligent.Keywords: agricultural machine, tea, harvesting, reciprocating cutter, model, design, experiment, optimizationDOI: 10.25165/j.ijabe.20211406.5519Citation: Han Y, Xiao H R, Song Z Y, Chen Q M, Ding W Q, Mei S. Design and experiments of 4CJ-1200 self-propelled tea plucking machine. Int J Agric & Biol Eng, 2021; 14(6): 75–84.